2020
DOI: 10.1186/s12870-020-02351-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of Secale africanum chromosome 6Rafr in wheat enabled localization of genes for resistance to powdery mildew and stripe rust

Abstract: Background: Introgression of chromatin from Secale species into common wheat has for decades been a successful strategy for controlling the wheat diseases. The wild Secale species, Secale africanum Stapf., is a valuable source for resistance to foliar disease of wheat. A wheat-S. africanum chromosome 6R afr substitution line displayed resistance to both powdery mildew and stripe rust at the adult-plant stage. Results: Wheat-S. africanum chromosome 6R afr deletion and translocation lines were produced and ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 47 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…Some powdery mildew resistance genes have been reported from chromosome 6RL of rye cultivars including Prolific, Jingzhouheimai, and Kustro, among which the resistance gene from Kustro was localized in the region from the site between 2.3 and 2.5 to the telomere ( Friebe et al, 1994 ; Wang et al, 2010 ; Li et al, 2016 ; Du et al, 2018 ). A powdery mildew APR gene(s) from the wild species Secale africanum was mapped on the long arm of 6R afr at FL0.85–1.00 ( Li G.R. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some powdery mildew resistance genes have been reported from chromosome 6RL of rye cultivars including Prolific, Jingzhouheimai, and Kustro, among which the resistance gene from Kustro was localized in the region from the site between 2.3 and 2.5 to the telomere ( Friebe et al, 1994 ; Wang et al, 2010 ; Li et al, 2016 ; Du et al, 2018 ). A powdery mildew APR gene(s) from the wild species Secale africanum was mapped on the long arm of 6R afr at FL0.85–1.00 ( Li G.R. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, based on the breakpoints revealed by Synt2, Synt6, and sequential ND-FISH, we found that the FL 0.85-1.00 segments of chromosomes 6R a L and 6R s L of S. africanum and S. sylvestre, respectively, most likely belonged to linkage group 2. Li et al (2020a) physically localized a Pm gene in that region, and thus it is likely that the gene may be traced to the linkage group 2L region of S. africanum. Therefore, we propose that the bulked probes could assist in locating breakpoints of non-homologous regions for physical dissection of rearranged regions carrying useful genes transferred from Secale to wheat.…”
Section: Discussionmentioning
confidence: 99%
“…The seeds were placed in a sterilized germination box and cultured in the dark at 25 °C for 24 h in an incubator. At 9 a.m. the next day, the germination box was placed in an incubator at 15 °C for 12 h in the dark, and at 9 p.m., the germination box was placed in an incubator at 25 °C for 12 h in the dark according to the method of Li [ 37 ] and Lang [ 38 ]. At 9 a.m. on the third day, we took a 1–2 cm root tip from the ultra-clean workbench and put the moist root tip into a 1.5 mL centrifuge tube (the cap was pierced with a red-hot dissecting needle) and put it in nitrous oxide for 2 h. Afterward, we added acetic acid to the centrifuge tube and fixed it for 5 min.…”
Section: Methodsmentioning
confidence: 99%